FGF23-related hypophosphatemia in a patient with small cell lung cancer: a case report and literature review - Hajime Kato; Soichiro Kimura; Maho Taguchi; Takashi Sunouchi; Yoshitomo Hoshino; Naoko Hidaka; Nadia Edvige Foligno; Minae Koga; Katsunori Manaka; Hiroyuki Tamiya; Masanori Kawakami; Hidenori Kage; et al. (Endocrine Journal)
Although there are a few case reports of patients with small cell lung cancer developing hypophosphatemia, detailed information on this condition is scarce. A 52-year-old patient with advanced stage small cell lung cancer developed hypophosphatemia (1.1 mg/dL) during chemotherapy. A reduced level of the tubular reabsorption of phosphate concomitant with an inappropriately elevated level of fibroblast growth factor (FGF) 23 (48.4 pg/mL) was noted, leading to the diagnosis of FGF23-related hypophosphatemia. Laboratory data also showed hypercortisolemia with an elevated ACTH level and hyponatremia with an inappropriately unsuppressed level of antidiuretic hormone (ADH). These data suggested the overproduction of FGF23 in addition to ACTH and ADH. Because the octreotide loading test did not present a suppressive effect on ACTH or FGF23 levels, the patient was treated with phosphate supplementation, active vitamin D and metyrapone, which partially improved the serum phosphate and cortisol levels. Even after two subsequent courses of chemotherapy, the small cell lung cancer progressed, and the FGF23 level was further elevated (83.7 pg/mL). Although it is very rare, FGF23-related hypophosphatemia is one of the hormonal disturbances that could be observed in patients with small cell lung cancer. This article reviews similar clinical conditions and revealed that advanced states of malignancy seemed to be associated with the development of renal wasting hypophosphatemia, especially in lung cancer and prostate cancer. Therefore, the parameters related to hypophosphatemia should be monitored in patients with advanced small cell lung cancer to prevent the development of hypophosphatemic osteomalacia.